Penggunaan kitosan sebagai pengisi dalam pembuatan sabun transparan : The utilization of chitosan as a filler for transparency soap - Ibrahim, Bustami; Suptijah, Pipih; Amin, Hijrah (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2010)
Chitosan is a natural material extracted from deacetylated chitin of crustacean shell used for many kinds of functions, not only for food but also non food product. The research objective is to find out the effect of chitosan used for filler within transparency soap to the characteristic of physical, chemical and bioeffect of end product, and to find out which concentrate of chitosan will be used for the best product. The research was divided by two steps, pre-research and main research. Pre-research resulted that transparency soap with 5% chitosan was the best choice based on organoleptic test which was the best in toughness, and based on chemical also microbiological analyses. The soap with 5% chitosan has TPC (Total Plate Count) amount to 2.0x101, while the one without chitosan contained TPC 6.5x101. The main research showed that transparency soap with 5% chitosan has better quality compare to commercialized one.